The politics of belonging intersectional contestations - Yuval-Davis, Nira (London Sage, 2011)
"In this groundbreaking book, Nira Yuval-Davis provides a cutting-edge investigation of the challenging debates around belonging and the politics of belonging. Alongside the hegemonic forms of citizenship and nationalism which have tended to dominate our recent political and social history, the author examines alternative contemporary political projects of belonging constructed around the notions of religion, cosmopolitanism, and the feminist 'ethics of care'. The book also explores the effects of globalization, mass migration, the rise of both fundamentalist and human rights movements on such politics of belonging, as well as some of its racialized and gendered dimensions. A special space is given to the various feminist political movements that have been engaged as part of or in resistance to the political projects of belonging. The author deconstructs notions of national and ethnic and interrogates the effects that different political projects of belonging have on members of these collectivities who are differentially located socially, economically, and politically. The Politics of Belonging will appeal to students and researchers in a range of disciplines including women's and gender studies, sociology, cultural studies, theology and religious studies, and political science."--Publisher's website.
Introduction: framing the questions -- The citizenship question: of the state and beyond -- The national question: from the indigenous to the diasporic -- The religious question: the sacred, the cultural and the political -- The cosmopolitan question: situating the human and human rights -- The caring question: the emotional and the political -- Concluding remarks.
Includes bibliographical references (pages [207]-247) and index.
Keywords: Social integration; Group identity